More fun with foam, on my own: great kids'accessories made with precut foam shapes - Gerig, LeNae (Hot Off The Press Oregon, 2003)
More Fun with Foam, On My Own: Made with Precut Foam Shapes is a creative activity book that provides step-by-step instructions for making a variety of crafts using pre-cut foam shapes. Perfect for young children, this book encourages imagination and fine motor skills while offering hours of fun and entertainment.